Seropositive for hepatitis B and C viruses is associated with the risk of decreased bone mineral density in adults: An analysis of studies from the NHANES database - Tao, Jiasheng; Yan, Zijian; Huang, Wenmian; Feng, Tao (Frontiers in Medicine, 2023)
Background Some reports have reported that the patients with viral hepatitis are at increased risk of reduced bone mineral density and even osteoporosis. However, the interaction between reduced bone mineral density (BMD) and viral hepatitis remains inconclusive. Therefore, our study collected hepatitis test results and bone mineral density from respondents in the NHANES database. The aim is to investigate whether there is an association between hepatitis and a decrease in bone mineral density. Methods The respondents with both hepatitis and BMD related indicators from the NHANES database in the USA from 2005-2010,2013-2014 and 2017-2020 are collected for this study. Comparisons are made between respondents who were positive and negative for respondents related to hepatitis B and C. BMD is measured by using dual-energy X-ray absorptiometry of the femur and lumbar spine. Finally, multiple regression analysis is performed between hepatitis B surface antigen (HBsAg) and hepatitis C RNA (HCV-RNA) and BMD in the respondents. Results A total of 15642 respondents are included in the hepatitis B surface antigen related survey. Of these, 1217 respondents are positive for hepatitis B surface antigen. Hepatitis C RNA related respondents are included in a total of 5111. Hepatitis C RNA-positive have 268 respondents. According to the results of the multiple regression analysis, the femoral BMD is significantly lower in HBsAg(+) respondents compared to HBsAg(-) respondents -0.018 (-0.026, -0.009)(P＜0.01). Also, spinal BMD is significantly lower in HBsAg(+) respondents compared to HBsAg(-) respondents -0.020 (-0.030, -0.010)(P＜0.01). On the results of multiple regression analysis for hepatitis C RNA, HCV-RNA (+) respondents have significantly lower BMD compared to HCV-RNA (-) respondents -0.043 (-0.059, -0.026)(P＜0.01). Conclusions In the analysis of respondents in the NHANES database in the USA, the positive tests for hepatitis B surface antigen and hepatitis C RNA are found to be associated with a reduction in BMD. Positive serology for these hepatitis indicators may increase the risk of reduced BMD. Of course, this conclusion still needs to be further confirmed by more large clinical trials.